Revolt Against Modernity - Ted V. McAllister (1996)
Eric Voegelin and Leo Strauss are two of the most provocative and durable political philosophers of this century. Ted McAllister's superbly written study provides the first comprehensive comparison of their thought and its profound influence on contemporary American conservatism.